Promoting Self-Determination in Health for People with Intellectual Disabilities through Accessible Surveys of their Healthcare Experiences - White, Alexa; Liberatos, Penny; O’Hara, David; Davies, Dan; Stock, Steven (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2015)
Increasingly our knowledge of how to provide effective health care finds itself concerned about how to improve health literacy and increase patient engagement in, and self-management of, their health care experience. For people with intellectual and developmental disabilities (IDD) addressing these issues requires some innovative solutions. The Westchester Institute for Human Development (WIHD), a university center of excellence in disability education, research and service, is a comprehensive health care provider to over 5,000 adults with IDD. WIHD is committed to ensuring that health information technologies are designed and used in ways that enhance self-determination in health care for people with IDD. As part of its work in developing accessible health information technologies WIHD supported a research project designed to convert an existing US Federal Government survey of a patient’s experience of their health care into an electronic format that enabled direct responses to survey questions by the patient with IDD. This article discusses the research process, findings and success of this accessible patient experience survey technology project and its implications for future technology innovation designed to improve selfdetermination in health care for people with IDD. The survey in question was the US Agency for Health Care Quality and Research Consumer Assessment of Providers and Systems (CAHPSD) patient experience survey.